BATAKO RINGAN DENGAN CAMPURAN LIMBAH AMPAS SAGU - Latuconsina, MOH. HUSAIN ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Sago waste is an organic materials, which is derived from industrial processing of sago flour in Maluku that consist of 25% sago flour, and the 75% is waste. The waste of sago industry has not been completely resolved, thus it causes negative impact to the environment, also along the river in vicinity. Some researches have been conducted using organic waste, one of the research is wood sawdust for concrete brick. Study on lightweight concrete brick using sago waste aims to create building material that is lighter and economist, also to minimize negative impact of the waste to the environment. Test object of lightweight concrete brick uses ratio of 1 part of cement and 6 parts of sand (1:6), where the volume of sand to sago waste is 0%, 25%, 50%, 75% and 100%. The process of test object making starts from basic material testing of sand and sago waste, and then it is weighed according to the test object needed for the study. These materials are mixed and molded in the form of bricks and treated in the water submersion. The 28 days brick will be performed in a series of tests including density, compressive strength and water absorption. The research result shows that compressive strength of lightweight brock of each compositions are 67,003 kg/cm2; 46,533 kg/cm2; 19,556 kg/cm2; 7,248 kg/cm2; and 2,669 kg/cm2. The mixture composition of 25% sago waste with compressive strength value of 46,533 kg/cm2 meets the minimum quality standard of concrete block compressive strength type III according to SNI standard No. 03-0349-1989. Density of each mixture compositions are 1,986 g/cm3; 1,876 g/cm3; 1,635 g/cm3; 1,334 g/cm3; and 1,097 g/cm3. Water absorption value of each mixture compositions are 10,652%; 13,371%; 14,960%; 22,972%; and 32,421%.